Artificial Neural Network Utilization for FSO Link Performance Estimation - M. Mudroch; S. Zvanovec (Radioengineering, 2014)
This paper describes FSO link performance prediction based on available meteorological data using different Artificial Neural Network (ANN) approaches. Several types of ANNs were compared and their performance were evaluated. The paper introduces an ANN application utilizing real delayed data. This approach has been validated to be more precise than common feed-forward neural networks.